Gk with Derek the ultimate general knowledge and quiz compendium: sports and cinema - O'Brien, Derek (Penguin Books, 2004)
Gk with Derek the ultimate general knowledge and quiz compendium: sports and cinema / O'Brien, Derek. -- New Delhi: Penguin Books, 2004 001 Obr13 V6 No. of Copies : 2